Sensor to sensor calibration of the integrated INS/vision navigation system: Time-domain optimization. (23rd June 2017) - Yang, Dongfang; Sun, Dawei; Liu, Yang; Liao, Shouyi
Due to the essential limitation of optical sensors, its integration with traditional Inertial Navigation System (INS) tends to be the focus in indoor navigation applications. In a low-cost INS/vision integrated navigation system, the relative position and gestures between slave systems are important coefficients. In order to solve the initial bias estimation problems involved in INS/vision integrated system, this article proposes a novel alignment approach based on the time-domain constraints. At first, on the basis of traditional initial alignment model, the time-domain constrained model is deduced, in which the time-related states and measurements are all modeled. In order to verify the advantage of state evaluability, both the traditional alignment model and the corresponding time-domain constrained model are analyzed via the nonlinear observability analysis method. At the end of this article, two groups of numerical simulations are implemented, and the corresponding results validate the effectiveness of the proposed time-domain constrained model.